2017
DOI: 10.1002/term.2220
|View full text |Cite
|
Sign up to set email alerts
|

A novel system for expansion and delivery of human keratinocytes for the treatment of severe cutaneous injuries using microcarriers and compressed collagen

Abstract: Cell therapy with autologous or allogeneic keratinocytes applied as a single-cell suspension is well established in clinical practice in the treatment of severe burn injuries to augment epithelial barrier restoration. Yet, the application of cell sprays can lead to significant cell loss owing to lack of adhesion of cell suspension to the wound bed. The development of a robust and controllable method of transplanting cells onto the wound bed is yet to be established. The ability to control adhesion and distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The total cell number within each CM is simply controlled by the volume and cell density of the wrapped suspension droplets, while the CM size can be tailored by varying the volume of the liquid core from 3 µl to 15 µl. Robust and accurate control of cell release and delivery is crucial for the success of cell transplantation (Martin et al, 2017). Our research has demonstrated that the CMs were mechanically strong enough to be handled as 'soft solids', thus accurate delivery was achieved by transferring the CMs into very distinct culture systems using sterilised forceps.…”
Section: Discussionmentioning
confidence: 96%
“…The total cell number within each CM is simply controlled by the volume and cell density of the wrapped suspension droplets, while the CM size can be tailored by varying the volume of the liquid core from 3 µl to 15 µl. Robust and accurate control of cell release and delivery is crucial for the success of cell transplantation (Martin et al, 2017). Our research has demonstrated that the CMs were mechanically strong enough to be handled as 'soft solids', thus accurate delivery was achieved by transferring the CMs into very distinct culture systems using sterilised forceps.…”
Section: Discussionmentioning
confidence: 96%
“…Our culture time was somehow longer than what have been reported before (12 -21 days) [9,28,29,32]. Alternatives to the classical CAK, tissue-engineered products that combine keratinocytes with other cell types, micro barriers, or scaffolds could be considered [22,31,[33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of fibroin as a support for cell growth was considered a suitable approach for MSCs culture to provide not only a good cellular expansion but also a good maintenance of cell proliferation and differentiation capability [54,55,56,57,58]. Finally, microcarriers were defined as a suitable cell delivery system since they can be directly injected locally, ensuring the maintenance of cells at the target site while minimizing patients’ discomfort [25,59,60].…”
Section: Discussionmentioning
confidence: 99%